LIBRARY RESEARCH: A HISTORICAL-REFLECTIVE ANALYSIS OF THE CHANGES IN THE PARADIGM OF INDONESIAN EDUCATION FROM THE BEGINNING OF INDEPENDENCE TO THE DIGITAL ERA - Puput Tri Anggara; Rukiyati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study examines the paradigm shift in Indonesian education from independence to the digital era through a literature review employing a historical-reflective approach. This study aims to trace the dynamics of national education development and understand how the humanistic values ​​that have been the foundation of education since independence have transformed to face the demands of modernization and technology. Library research methods involve examining scientific articles, historical documents, and related publications to identify patterns of policy change, curriculum focus, and educational orientation. The results show that each historical phase has its own emphasis: the early independence period focused on the formation of national character, the New Order emphasized curriculum stability and centralization, the Reformation era introduced decentralization and flexibility in education, while the digital era demands technological literacy, 21st-century competencies, and the strengthening of digital ethics. Although digitalization opens up opportunities for more flexible and collaborative learning, gaps in infrastructure and educator capacity remain challenges that can widen disparities in education quality between regions. This study emphasizes the importance of integrating historical, humanistic, and technological innovation values ​​to realize an education that is adaptive, inclusive, and relevant to future needs.